2010
DOI: 10.1021/ja1058247
|View full text |Cite
|
Sign up to set email alerts
|

Cp* Iridium Complexes Give Catalytic Alkane Hydroxylation with Retention of Stereochemistry

Abstract: A series of Cp*Ir complexes can catalyze C-H oxidation, with ceric ammonium nitrate as the terminal oxidant and water as the source of oxygen. Remarkably the hydroxylation of cis-decalin and 1,4-dimethylcyclohexane proceeds with retention of stereochemistry. With H(2)O(18), cis-decalin oxidation gave (18)O incorporation into the product cis-decalol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 15 publications
2
85
0
Order By: Relevance
“…Since then a wide number of molecular iridium precursors have been reported, with half sandwich iridium compounds showing the highest activities ,. Although the exact nature of the active species is still a matter of debate, it has been shown that the Cp*Ir III complexes are precursors which undergo oxidative activation with loss of the Cp* ligand, either chemically, or electrochemically, before entering catalysis . A crucial feature of the most effective members of that family is an oxidatively robust chelate ligand that remains bound to the iridium to prevent decomposition into IrO x and modulates the active site ,.…”
Section: Introductionmentioning
confidence: 99%
“…Since then a wide number of molecular iridium precursors have been reported, with half sandwich iridium compounds showing the highest activities ,. Although the exact nature of the active species is still a matter of debate, it has been shown that the Cp*Ir III complexes are precursors which undergo oxidative activation with loss of the Cp* ligand, either chemically, or electrochemically, before entering catalysis . A crucial feature of the most effective members of that family is an oxidatively robust chelate ligand that remains bound to the iridium to prevent decomposition into IrO x and modulates the active site ,.…”
Section: Introductionmentioning
confidence: 99%
“…11,12,2022 Both Cp* (Cp* = pentamethylcyclopentadienyl) and Cp (Cp = cyclopentadienyl) half-sandwich Ir III complexes are viable precatalysts, not only for water oxidation but also selective CH oxidations. 23,24 We have used NaIO 4 as a primary oxidant in this chemistry because of its ease of handling, good solubility, and lack of absorptions in the visible and near-UV. The disadvantage is that we cannot be certain if the reaction catalyzed in this case is true water oxidation rather than periodate dismutation: 2 IO 4 − → 2 IO 3 − + O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The translation of lab-scale aqueous procedures ('in water' 'on water' or 'by water' 81 ) to the industrial level can be seen in the same 'green' light, courtesy in part to the design of water-soluble reagents: note, for example, the application of copper sulfonatosalen complexes for amination of aryl halides in water 82 and copper 2-pyridylaldoxime complexes for the the aqueous conversion of aryl halides to phenols 83 . Looking more abstractly at the current highlights, mention might be given to developments in alkane oxidation: note the angular hydroxylation of bicyclic hydrocarbons with Ce(IV) and a catalytic amount of Ir(III) 84 , and the aerobic oxidation of cycloalkanes with robust copper-containing ceramic material (Cu@SiCN), in which the copper content can be simply varied to adjust selectivity 85 . An interesting terminal functionalization of alkanes in one pot is also at hand via iridium-catalyzed dehydrogenation to the terminal alkene and subsequent regiospecific hydrozirconation prior to electrophilic substitution 86 .…”
Section: Further Trends and Developments In Synthetic Organic Chemistmentioning
confidence: 99%